Keterbatasan Kuota Perempuan di Parlemen Lokal Indonesia: Analisis Kondisi Kultural dan Institusional Yang Mempengaruhi Rendahnya Keterwakilan Perempuan di DPRD Jawa Tengah - Solkhah Mufrikhah (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
This study is about the limitation of the gender quota (women's quota) and the problem of low representation of women in the Central Java DPRD in the 2019 Election. This study is inspired by the phenomenon of low representation of women including Indonesia, especially Central Java, despite various policies of avirmative action in the form of a 30 percent gender quota. both in parliament, as well as in the organizational structure of political parties and the list of candidates proposed by each party to compete for parliamentary seats in Indonesia, both at the national and local levels. To reveal this problem, this study was conducted to answer two research questions, namely: first, why was women's representation (electability) in the Central Java DPRD low in the 2019 elections ?and second, what cultural and institutional conditions hampered women's representation (electability) in the DPRD Central Java in the 2019 elections? In answering the two questions above, this study uses qualitative methods and a case study approach. Meanwhile, gender theory stereotypes and supply and demand models are used as analytical frameworks. Where the results of this study found that the low representation of women in the Central Java DPRD 2019 Election results was caused by the following factors. First, socio-cultural factors, where the patriarchal system and negative stereotypes on women still dominate the socio-cultural life of the people in Central Java. Patriarchal culture is not only strong in the socio-cultural system of society, but also in the internal organization of political parties. The second factor is the institutional conditions that exist in political parties and the electoral system adopted by the Indonesian government in the implementation of the 2019 legislative elections. Studi ini tentang keterbatasan gender quota (kuota perempuan) dan problem rendahnya keterwakilan perempuan di DPRD Jawa Tengah hasil Pemilu 2019. Studi ini diilhami dari fenomena rendahnya keterwakilan perempuan di termasuk Indonesia, khususnya Jawa Tengah, meskipun beragam kebijakan avirmative action dalam bentuk gender quota 30 persen baik dalam parlemen, maupun dalam struktur organisasi partai politik dan daftar pencolan para kandidat yang diajukan oleh setiap partai untuk memperebutkan kursi parlemen di Indonesia, baik di tingkat nasional maupun lokal. Untuk mengungkap masalah tersebut, penelitian ini dilakukan untuk menjawab dua pertanyaan penelitian, yaitu: pertama, mengapa keterwakilan (keterpilihan) perempuan di DPRD Jawa Tengah rendah pada pemilu 2019?; dan kedua, kondisi-kondisi kultural dan institusional seperti apa yang menghambat keterwakilan (keterpilihan) perempuan di DPRD Jawa Tengah pada pemilu 2019? Dalam menjawab dua pertanyaan di atas, penelitian ini menggunakan metode kualitatif dan pendekatan studi kasus. Sedangkan teori gender stereotype dan supply and demand model digunakan sebagai kerangka analisis. Dimana hasil penelitian ini menemukan bahwa rendahnya keterwakilan perempuan di DPRD Jawa Tengah hasil Pemilu 2019 disebabkan oleh beberapa faktor berikut. Pertama, faktor sosial budaya, dimana sistem patriarki dan stereotir negatif pada perempuan masih kuat mendominasi kehidupan sosial budaya masyarakat di Jawa Tengah. Budaya patriarki tidak saja kuat dalam sistem sosial budaya masyarakat, namun juga kuat dalam internal organisasi partai politik. Faktor kedua, adalah kondisi-kondisi institusional yang ada dalam partai politik maupun sistem pemilu yang diadopsi oleh pemerintah Indonesia dalam pelaksanaan Pemilu legislative2019.